The ugly truth (Sony Pictures Home Entertainment, 2009)
The search for 'Mr. Right' has left Abby, a romantically challenged morning show producer, hopelessly single. She receives an eye-opening education when she gets teamed up with Mike, a hardcore TV personality, who wants to prove his theories on what makes men tick by helping her find true love. The unexpected results may surprise them both.